Must love dogs - Lane, Diane; Goldberg, Gary David; Cusack, John, 1966-; Mulroney, Dermot; Perkins, Elizabeth, 1960-; Channing, Stockard; Bailey, John, 1942 August 10-; Armstrong, Craig, 1959-; Cook, Claire, 1955-; Warner Home Video (Firm) ([Burbank, CA] : Warner Home Video, 2005)
Sarah Nolan is divorced, demoralized and dateless - until her sister posts her profile on perfectmatch.com. Now she has a lot of dates, mainly with weirdos, weepers, lechers and jocks. Then she meets Jake, a soulful boat builder whose idea of true love comes straight from the movies. Jake is attractive, smart and maybe a bit too intense for Sarah, so she passes him by. But in passing him up, she may be passing up a real chance for love.
Based on the book by Claire Cook.
Special features: Additional scenes with optional commentary; "Pass the beef" gag reel; theatrical trailer.
Director of photography, John Baily ; editor, Eric Sears ; music, Craig Armstrong ; costume designer, Florence-Isabelle Megginson, Gamila Smith ; production designer, Naomi Shohan.
Diane Lane, John Cusack, Dermot Mulroney, Elizabeth Perkins, Stockard Channing, Christopher Plummer.
MPAA rating: PG-13; for sexual content.
DVD, region 1, full screen (1.33:1) presentation.
Keywords: Man-woman relationships -- Drama; Online dating -- Drama; Love -- Drama; Relaciones humanas -- Teatro; Amor -- Teatro; Feature films; Romance -- Feature; Comedy -- Feature; Films for the hearing impaired; Videodiscs